2015
DOI: 10.1021/acsami.5b08124
|View full text |Cite
|
Sign up to set email alerts
|

Distance-Based Tear Lactoferrin Assay on Microfluidic Paper Device Using Interfacial Interactions on Surface-Modified Cellulose

Abstract: "Distance-based" detection motifs on microfluidic paper-based analytical devices (μPADs) allow quantitative analysis without using signal readout instruments in a similar manner to classical analogue thermometers. To realize a cost-effective and calibration-free distance-based assay of lactoferrin in human tear fluid on a μPAD not relying on antibodies or enzymes, we investigated the fluidic mobilities of the target protein and Tb(3+) cations used as the fluorescent detection reagent on surface-modified cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 47 publications
1
83
0
Order By: Relevance
“…Recently, microfluidic paper-based analytical devices (μPADs) have attracted a lot of attention and have been actively developed due to being simple, inexpensive, user-friendly, and disposable. [12][13][14][15][16] To date, μPADs have been used as elegant analytical tools for a variety of applications, including medical diagnosis, [17][18][19][20][21] food testing, 22 and environmental monitoring. [23][24][25][26][27][28][29] A lot of detection methods have been used for μPADs.…”
Section: Crmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, microfluidic paper-based analytical devices (μPADs) have attracted a lot of attention and have been actively developed due to being simple, inexpensive, user-friendly, and disposable. [12][13][14][15][16] To date, μPADs have been used as elegant analytical tools for a variety of applications, including medical diagnosis, [17][18][19][20][21] food testing, 22 and environmental monitoring. [23][24][25][26][27][28][29] A lot of detection methods have been used for μPADs.…”
Section: Crmentioning
confidence: 99%
“…The most common detection method for μPADs is colorimetry because analysis is relatively simple. Moreover, there are various techniques of the fabrication of μPADs, such as wax printing, 23,26,27,[29][30][31][32] inkjet printing, 17 screen printing, 18,22 and photolithography. 24 With regard to Cr analysis using μPADs, several methods have been reported.…”
Section: Crmentioning
confidence: 99%
“…These techniques include time-based, [9][10][11][12] distancebased, [13][14][15][16] and titration-based detection. [17][18][19] Philips and coworkers demonstrated time-based detection using an enzymatic reaction wherein a color change took place at different times depending on the concentration of the analyte.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Conversely, some research groups have developed distance-based PADs that permit the quantitation of analytes without the use of either a scanner or a digital camera, since the amount of the analyte could be determined by reading the distance of the color bar evolving on the PAD. [13][14][15][16] Zhang and coworkers employed both the time and the number of the detection zones that changed color. 11,12,20 We also reported that titrimetric PADs where the endpoint is judged using only the naked eye to count the number of detection zones.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] The type and model of the optical recorder, as well as the ambient light condition, remain issues in achieving a reproducible and accurate quantitative assay. As a result, alternative ideas, such as utilizing the reaction band-length of the color zone, 17,[23][24][25] the number or position of colored regions 26 or measuring the time from sample introduction until the appearance of a particular phenomenon 27 have been proposed. The application of μPADs with detection of the reaction bandlength has been demonstrated for several classes of clinically or environmentally relevant analytes, including the determination of serum glucose and glutathione, 17 tear lactoferrin, 23 airborne metals (Ni, Cu, Fe) in welding fumes 24 and Cu ion in drinking water.…”
Section: Introductionmentioning
confidence: 99%